PERBANDINGAN HUKUM ARBITRASE DAN ALTERNATIF PENYELESAIAN SENGKETA ARBITRASE ONLINE INDONESIA DAN CINA - Afrizal Mukti Wibowo (Audito Comparative Law Journal (ACLJ), 2021)
This article focuses on legal comparisons between Indonesian law and China law regarding arbitration and alternative dispute resolution, especially online arbitration. The author sees a similarity in terms of law, namely that there is no single law regulating the use of online arbitration. Even more, the conditions of the Covid-19 pandemic focused alternative dispute resolution to be carried out online as well. This paper is normative legal research with a comparative approach. The results of this paper are neither in Indonesia nor China regulates online arbitration in their legal system, but both provide opportunities for online arbitration to be held. There are differences in Indonesia and China. In Covid-19 pandemic situation force BANI Arbitration Center implemented online arbitration. But in China, China International Economic and Trade Arbitration Commission (CIETAC) fully implement online arbitration before covid-19 pandemic.